Extreme compression behaviour of higher derivative properties of solids based on the generalized Rydberg equation of state - Shanker, J.; Singh, B.P.; Jitendra, K. (Condensed Matter Physics, 2009)
We have derived formulations for the pressure derivatives of bulk modulus up to the third order and for higher
order Gr¨uneisen parameters using the generalized free volume theory, and the generalized Rydberg equation
of state. The properties derived in the present study are directly related to the understanding of thermoelastic
properties of solids. The third order Gr¨uneisen parameter (lambda λ) in the limit of in nite pressure has
been found to approach a positive finite value for lambda in nity (λ∞) equal to 1/3. This is a result shown
to be independent of the value of K-prime in nity, i. e., the pressure derivative of the bulk modulus at infinite
pressure. The results based on other equations of state have also been reported and discussed. We find a
relationship between λ∞ and pressure derivatives of bulk modulus at infinite pressure which is satisfied by
different types of equations of state. Ми отримали формулювання для похiдних третього порядку за тиском вiд об’ємних модулiв i для параметрiв Грюнайзена вищого порядку, використовуючи узагальнену теорiю вiльного об’єму та узагальнене рiвняння стану Рiдберга. Отриманi властивостi є безпосередньо пов’язаними iз розумiнням термоелектричних властивостей твердих тiл. Показано, що параметр Грюнайзена третього порядку (λ) в границi нескiнченного тиску (λ∞) наближається до скiнченного позитивного значення, рiвного 1/3. Показано, що цей результат не залежить вiд значення похiдної за тиском вiд об’ємного модуля при нескiнченному тиску. Також обговорюються результати, отриманi на основi iнших рiвнянь стану. Ми знайшли спiввiдношення, що зв’язує λ∞ та похiднi за тиском вiд об’ємних модулiв при нескiнченному тиску, яке задовольняється для рiзних типiв рiвнянь стану.